Turning ‘Space’ into ‘Place’ with Food: Immigrant Women’s Food Narratives in Post-1945 North Bay, Ontario - Hough Evans, Jennifer (Ontario History, 2014)
This article on food, identity, and place-making, examines the lives of twelve immigrant women in post-1945 North Bay, Ontario. It demonstrates how these women, as they navigated their way through kitchen and grocery store spaces, negotiated their sense of place, in connection with their identities, their memories brought from home, and their material contexts.